Pharmacokinetics of curcumin in Thai healthy volunteers following Multiple Administration of curcuminoids tablets - Sineenart Sriphanichakit (Chulalongkorn University, 2014)
Thesis (M.Sc. in Pharm)--Chulalongkorn University, 2006